ORE-MAGMATIC SYSTEM SUKUMALAND (TANZANIA) - Mykhailov, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The overwhelming part of the gold ore potential of the United Republic of Tanzania is confined to the systems of the Neoarchaean greenstone belts (GSB) of the metallogenic province of Lake Victoria in the northwestern part of the country. Based on the interpretation of space imagery, in the western part of the province the Sukumaland ore-magmatic system of concentric-zonal structure has been distinguished. It is formed by a group of arched greenstone belts and associated gold deposits. They form two arcuate branches: the internal and external branch, differing in their composition and structure. The internal arc is represented by the Rwamagaza and Kahama GSB with gold deposits of Tulawaka, Buckreef, Mawe-Meru, Tembo, and Bulyanhulu. The external arc is represented by Geita and Mabale-Buhungurica GSB with gold deposits of Ridge-8, Nyankanga, Geita, Matandani, Kukuluma, Nyanzaga, Kitongo, Golden Ridge, Nyakafuru, and Miabu. Their huge gold potential (over 50 million ounces of gold) stipulates for the urgency of the study of this gigantic structure. GSB of the inner arc (Rwamagaza and Kahama) are characterized by a predominance of basic volcanic rocks, and GSB of the external arc (Geita and MabaleBuhungurica) – by sedimentary and volcanic-sedimentary formations, in particular, banded ironstone formations (BIF). Accordingly, gold deposits of the inner arc are mainly associated with basic volcanic rocks (Tulawaka, Buckreef, Mawe-Meru, Bulyanhulu, Tembo) while gold deposits of the external arc – with BIF (Geita, Nyankanga, Kukuluma, Matandani). The nuclear part of the ore-magmatic system is of special interest, although manifestations of volcanism are absent there and gold or other mineral deposits are unknown yet, but a tectonic pattern of its structural elements indicates its significant ore potential. In particular, the presence of numerous spatially close systems of radial-circular faults attests to the presence of weakened zones in the space above the core of a hypothetical magma chamber. Gold deposits of different geological and industrial types, yet undiscovered, as well as manifestations of diatreme magmatism may be associated with these weakened zones. In particular, one cannot exclude the possible presence of diamond-bearing volcanic pipes. It is assumed that the ore-magmatic system has originated and evolved in the course of a complex multi-stage ore-magmatic process under the influence of ascending flows of depth fluids due to the long-term functioning of a zone with anomalously heated mantle in that area. During further geological exploration it is recommended to take into account the predictable availability of a single integrated ore-magmatic system of longdevelopment and its structural features.
Keywords: ore-magmatic system; greenstone belt; gold deposit